Observing Ghana’s food system transformation through an assessment of processed food retail in four major cities - Andam, Kwaw S.; Tschirley, David; Asante, Seth; Al-Hassan, Ramatu M.; Diao, Xinshen (2017)
This paper describes key features of processed food retail within the context of food system transformation in Ghana—the spread of supermarkets, the sources of processed food products, and the use of traditional and modern retail outlets as marketing channels. The data come from retail inventories of packaged products— poultry meat and eggs, processed tomatoes, and milled grains, roots, and tubers— in four major cities. We find that the interplay of urbanization, imports, and domestic processing and packaging has led to some surprising outcomes. Imports are dominant, as expected, especially for products such as milled rice and tomato paste. Yet, remarkably, import shares are lower (63 percent) in Accra, the principal city, compared to more than 70 percent in three smaller cities, and imported products have higher shares in traditional retail outlets than in modern retail outlets.